Association of Cancer Diagnosis and Therapeutic Stage With Mortality in Pediatric Patients With COVID-19, Prospective Multicenter Cohort Study From Latin America - Dominguez-Rojas, Jesus Ángel; Vásquez-Hoyos, Pablo; Pérez-Morales, Rodrigo; Monsalve-Quintero, Ana María; Mora-Robles, Lupe; Diaz-Diaz, Alejandro; Torres, Silvio Fabio; Castro-Dajer, Ángel; Cabanillas-Burgos, Lizeth Yuliana; Aguilera-Avendaño, Vladimir; Cantillano-Quintero, Edwin Mauricio; Camporesi, Anna; et al. (Frontiers in Pediatrics, 2022)
Background In this study, we describe the clinical characteristics of pediatric patients with cancer and COVID-19 from multiple Latin American centers and risk factors associated with mortality in this population. Methods This study is a multicenter, prospective cohort study conducted at 12 hospitals from 6 Latin American countries from April to November 2021. Patients younger than 14 years of age that had an oncological diagnosis and COVID-19 or multisystemic inflammatory syndrome in children (MIS-C) who were treated in the inpatient setting were included. The primary exposure was the diagnosis and treatment status, and the primary outcome was mortality. We defined “new diagnosis” as patients with no previous diagnosis of cancer, “established diagnosis” as patients with cancer and ongoing treatment and “relapse” as patients with cancer and ongoing treatment that had a prior cancer-free period. Results Two hundred and ten patients were included in the study; 30 (14%) died during the study period and 67% of patients who died were admitted to critical care. Demographics were similar in survivors and non-survivors. Patients with low weight for age (<-2SD) had higher mortality (28% vs 3%, p= 0.019). There was statistically significant difference of mortality between patients with new diagnosis (36.7%), established diagnosis 1.4%) and relapse 60%), (p <0.001). Most patients had hematological cancers (69%) and they had higher mortality (18%) compared to solid tumors (6%, p= 0.p032). Patients with concomitant bacterial infections had higher mortality (40%, p=0.001). MIS-C, respiratory distress, cardiovascular symptoms, altered mental status and acute kidney injury on admission were associated with higher mortality. Acidosis, hypoxemia, lymphocytosis, severe neutropenia, anemia and thrombocytopenia on admission were also associated with mortality. A multivariate logistic regression showed risk factors associated with mortality: concomitant bacterial infection OR 3 95%CI (1.1- 8.5), respiratory symptoms OR 5.7 95%CI (1.7-19.4), cardiovascular OR 5.2 95%CI (1.2- 14.2), new cancer diagnosis OR 12 95%CI (1.3- 102) and relapse OR 25 95%CI (2.9- 214). Conclusion Our study shows that pediatric patients with new onset diagnosis of cancer and patients with relapse have higher odds of all-cause mortality in the setting of COVID-19.